Consumption of alcohol and tobacco in students of nursing - Telumbre-Terrero, Juan Yovani (2015)
Introduction. Nursing students are immersed in a risky and protective cultural context on drugs consumption, during their academic term and/or work as they face various physical, emotional and social situations that may increase the likelihood of consuming alcohol and tobacco as a way to mitigate these situations. The objective of this research was to determine the type of alcohol and tobacco consumption among nursing students. Method. The population consisted of 172 students of a Nursing program of two private universities in the metropolitan area of Monterrey, Nuevo Leon, Mexico. The design of this study is non-experimental cross-sectional. A Personal Data Document, which also included Alcohol and Tobacco consumption and a Questionnaire to identify Disorders for Alcohol consumption (AUDIT), was used. Results. It was identified that prudent consumption is predominant, followed by the dependent and harmful consumption. As for tobacco consumption, nonsmokers were predominant, followed by the experimental smokers, former smokers, users and dependent smokers. Conclusion. These results allow a better understanding about the magnitude of alcohol and tobacco consumption problem among college students, specifically among nursing students who will be future health professionals and act as educators and advocates for the adoption of healthy lifestyles in the general population.